Art express - Adams, Eileen; Bignell, Rosemary; Bower, Jane; Grahame, Judy; Kitto, Michelle Claire; Mathieson, Kevin (London A&C Black Publishers Ltd, 2009)
A new and complete Art and Design scheme for Primary Class Teachers. Everything you need to teach drawing, painting, printing. sculpture, digital media, collage and textiles.
Book 1 ages 5-6 -- Book 2 ages 6-7 -- Book 3 ages 7-8 -- Book 4 ages 8-9 -- Book 5 ages 9-10 -- Book 6 ages 10-11.
Keywords: Art -- Study and teaching (Elementary) -- Activity programs